Lightweight cement bricks manufactured with additional rice husks / Ismahani Marhalim ...[et al.] - Marhalim, Ismahani; Abdul Rahman, Nurul Aqilah; Norazlan, Nurraihan Fasihah; Muhammad, Arbanah; Mat Zin, Mazni
The research aims was to study the effect of rice husk ash to properties of lightweight bricks. The size of the brick is 215mm x 103mm x 65mm rectangular mold which is standard size brick. Lightweight bricks have been produced by sintering water, cement and rice husk. The dried rice husks were grinded to small particles and sieved into sizes I mm while cement was sieved into 90Fm to avoid from coagulate. Samples containing 0 wt%. 5 wt%. 10 wt%. 20 wt% and 25 wt% addition of rice husk have been heated in the oven at temperature of 50c for 4 hours, allowing effective organic burn out. These samples were tested using 4 tests which are bulk density, water absorption, compressive strength and Ultra Pulse Velocity. The result showed that the addition of rice husk increased the porosity of the sintered bricks. The bulk density test showed that the bulk density of the bricks decreases with the increasing of rice husk addition and for the water absorption test showed that the brick sample with 5% of rice husk addition has the lowest percentage of water absorption compared to the other bricks. The results showed the decrease in compressive strength with increasing of rice husk addition. The brick sample containing 5% of rice husk addition produce the best compressive strength compared to the other samples. The UPV test that was conducted showed that the highest pulse velocity measured is from 0% addition of rice husk, at 3030 m/s but it does not fall under the range of good quality bricks. 5% and 10% addition of rice husk reads at 2413 m/s and 2160 m/s which fall under the range. The bricks with addition of20% and 25% cannot be read due to sensitivity UPV equipment towards the high content of fibre from the rice husk. The conclusion for the tests that have been made showed that 5% addition of rice husk in a brick is the best compared to 0%, I 0%, 20% and 25% addition of rice husks.